ChemInform Abstract: Synthesis and Decarboxylative Wittig Reaction of Difluoromethylene Phosphobetaine. Issue 50 (10th December 2013) - Zheng, Jian; Cai, Ji; Lin, Jin‐Hong; Guo, Yong; Xiao, Ji‐Chang
Abstract Two phosphobetaines are prepared and used as convenient difluoroolefination reagents.